Courts without borders : law, politics, and U.S. extraterritoriality / Tonya L. Putnam. - Putnam, Tonya L. (Tonya Lee) (Cambridge University Press, 2016)
Courts without Borders is the first book to examine the politics of judicial extraterritoriality, with a focus on the world's chief practitioner: the United States. For much of the post-World War II era, the United States has been a frequent yet selective regulator of activities outside its territory, and US federal courts are often on the front line in deciding the extraterritorial reach of US law. At stake in these jurisdiction battles is the ability to bring the regulatory power of the United States to bear on transnational disputes in ways that other states frequently dislike both in principle and in practice. This volume proposes a general theory of domestic court behavior to explain variation in extraterritorial enforcement of US law, emphasizing how the strategic behavior of private actors is important to mobilizing courts and in directing their activities.